Effectiveness of Momentum Strategies in Cryptocurrency Markets: An Analytical Research for the Period of 2018 to 2023 - Karol WOJTOWICZ (Communications of International Proceedings, 2024)
Investors in financial markets seek to maximize returns and minimize risk. To this end, they seek investment strategies that will enable them to achieve above-average returns. Many strategies are based on stock market anomalies. Momentum is one such strategy. That strategy, involves selecting assets for the portfolio that have recently gained above-average rates of return. The phenomenon, which has been identified in a number of global stock markets, recommends investing in securities that achieved the highest rates of return over a period of 3 to 12 months and selling short the securities with the lowest returns. The main purpose of the article was to identify the effects of momentum strategies in the case of selected instruments of cryptocurrencies markets. The effectiveness of investments in selected cryptocurrencies was studied in period from 2018 to 2023. Cryptocurrency returns were determined using logarithmic rates of return. The various assets were classified into “winners” and “losers” and then, according to the momentum assumption, the investment returns for long and short positions were determined. The research results confirm the occurrence of the momentum effect popular on the stock exchange for the analyzed assets. Investments including both long and short positions generated positive rates of return in most cases. The effectiveness of the momentum strategy was higher for investments in cryptocurrencies classified as "winners". Short sales were characterized by lower rates of return and, in some subperiods, also negative results.
Keywords: cryptocurrency; momentum; investment; information efficiency